2019
DOI: 10.1039/c8nr09918a
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite-related (CH3NH3)3Sb2Br9 for forming-free memristor and low-energy-consuming neuromorphic computing

Abstract: Perovskite-related (CH3NH3)3Sb2Br9 exhibits forming free properties in memristor devices and low energy consuming artificial synaptic behavior for neuromorphic computing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 71 publications
2
95
0
Order By: Relevance
“…In this section, we pay our attention to recent progress in OIP‐based resistive switching memories 37,52,58,215‐225 . Previous studies have revealed that two mechanisms, ionic migration and charge trapping/detrapping, can account for the resistive switching behaviors of OIPs, 218,219 which guided a series of materials design.…”
Section: Organic‐inorganic Hybrid Materials For Resistive Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we pay our attention to recent progress in OIP‐based resistive switching memories 37,52,58,215‐225 . Previous studies have revealed that two mechanisms, ionic migration and charge trapping/detrapping, can account for the resistive switching behaviors of OIPs, 218,219 which guided a series of materials design.…”
Section: Organic‐inorganic Hybrid Materials For Resistive Memorymentioning
confidence: 99%
“…More interestingly, Yang et al also studied a lead‐free perovskite MA 3 Sb 2 Br 9 (Figure 30D), which not only implemented multilevel storage but also succeeded to mimic biological synaptic functions (Figure 30E). 225 They prepared an Ag/PMMA/MA 3 Sb 2 Br 9 /ITO memristor device, wherein the PMMA layer was inserted to suppress the exposure of MA 3 Sb 2 Br 9 film to oxygen and moisture in air. This memristor exhibited outstanding artificial synaptic characteristics, such as excitatory postsynaptic current, inhibitory postsynaptic current, long‐term potentiation, long‐term depression, and spike‐timing‐dependent plasticity (Figure 30F), which are promising for neuromorphic computing.…”
Section: Organic‐inorganic Hybrid Materials For Resistive Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…However, under light illumination, 81.8% was achieved only after 2000 learning phases, indicating considerably improved learning and memory capability. Yang et al reported an artificial synapse on the basis of the perovskite‐related MA 3 Sb 2 Br 9 memristor, [ 94 ] which could show EPSC, inhibitory postsynaptic current (IPSC), LTP, long‐term depression (LTD), and STDP behaviors. Kim et al reported an artificial synapse on the basis of the dual‐phase (Cs 3 Bi 2 I 9 ) 0.4 −(CsPbI 3 ) 0.6 perovskite memristor, [ 109 ] which could also show EPSC, IPSC, STP, STD, LTP, LTD, STDP, and spike‐width‐dependent plasticity (SWDP) behaviors.…”
Section: Halide Perovskite Memristor Applicationsmentioning
confidence: 99%
“…[ 4–12 ] Of these innovative nonvolatile memories, RRAM offers low power consumption, fast response speed, long retention time, high scalability, multistate data‐storage capability, and a simple metal‐insulator‐metal structure. [ 9,13,14 ] Information storage in the RRAM is achieved by altering the resistance of its insulator. The adjustable resistance of the insulator is achieved by forming metallic or defect filaments with low resistance either by electrochemical metal dissolution or by changing the valence charge of the insulator.…”
Section: Introductionmentioning
confidence: 99%